Funkcje sportu. Wybrane problemy = Functions of sport. Selected problems - Hajduk, Fabian (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Along with changes in the role of sport in a society, its functions strengthen, weaken or disappear. A renewal of the ancient idea of competition in sport in the realities of the nineteenth and twentieth centuries revealed the incompatibility of its objectives and generated the need to develop the new ones. The improvement of economic conditions of life and implementation of the need for innovation in sport changed sport competitions into spectacles of high public interest. Sport shows made it possible to separate the functions in the division into categories of participation. Other divisions of functions highlight the richness of the subject of interdisciplinary research on sport.
Keywords: sport; rola sportu; funkcja sportu